Regulasi Pemerintah dalam Pasar Modal pada Era Otoritas Jasa Keuangan (OJK) - Lukmanul Hakim (KEADILAN PROGRESIF, 2017)
The capital market is a very dynamic industry, attractive, constantly changing, which is one element that is a benchmark for economic progress of a country in which traits - traits industrialized countries as well as new industry is the capital market has been growing and developing well. Characteristics is a consequence of the need for an independent regulator and ready to face the dynamics of these changes. Based on Law No. 8 of 1995 on Capital Markets, guidance, regulation, and daily supervision conducted by Bapepam Capital Market which aims to achieve capital market activities orderly, fair and efficient and protect the interests of investors and the public. After the establishment of the Financial Services Authority in which the passing of Law No. 21 Year 2011 on the Financial Services Authority, the agency is an independent body replacing the oversight function performed by BAPEPAM.